MOBA GAMES IN EFL EDUCATIONAL SETTINGS FOR INTERCULTURAL LANGUAGE TEACHING - Ghaffour, Mohamed Toufik; Sarnou, Hanane (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
This paper unveils the relative merits of multiplayer online battle arena (MOBA) games in EFL educational settings for educational purposes, particularly rechecking the influence of League of Legends (LoL) on the EFL learners’ ICC. We have used Byram’s (1997) Model as a framework of assessment for thematic analysis, and both the Cultural Intelligence Scale (CQS), modified by Gozzoli and Gazzaroli (2018) and the Assessment of Intercultural Competence of Chinese College Students (AIC-CCS) by Wu et al. (2013) to ensure a consistent questionnaire. Our participants were 75 Algerian EFL learners (Males=86,7%, Females= 13,3%) from different educational levels, aged 20.08 (SD= 2.99). The results indicate a need to design a more convenient MOBA game as a replace for LoL, as well as adopting a flexible assessment continuous guidance to ensure appropriate ICC instruction.